Simultaneous and sequential enzymatic cascades for asymmetric synthesis of chiral beta-hydroxyamide derivatives promoted by alcohol dehydrogenases and nitrile hydratases - Everton A. Tordato; Shirley A. Castilho; Humberto M. S. Milagre; Cintia D. F. Milagre (Green Chemistry Letters and Reviews)
Asymmetric synthesis of optically pure (S)-3-hydroxy-3-phenylpropanamide derivatives from o-, m- and p-substituted benzoylacetonitrile was achieved by two enzymatic one-pot protocols, the simultaneous and the sequential two-step linear cascade promoted by alcohol dehydrogenase (ADH) and nitrile hydratase (NHase). A set of commercially available ADHs and NHases were individually screened, followed by the investigation of the impact of the order of the biocatalyst addition and the effect of the substrate’s substituent. While NHases were able to hydrate o-, m-, and p-substituted electron withdrawing and electron donating substituents, the ADH was selective for the p-substituted ones. To overcome the absence of ADH catalytic activity towards beta-ketoamides, a less active NHase was employed, and the desired p-substituted products were obtained in high conversions (>99%) and ee (>99%) in the simultaneous and sequential cascade modes. Both strategies lead to optically pure (S)-3-hydroxy-3-phenylpropanamide p-substituted derivatives without the isolation of intermediates, minimizing the environmental impact and offering a greener approach.